Quality of survival assessment in European childhood brain tumour trials, for children below the age of 5 years. (March 2020) - Limond, J.; Thomas, S.; Bull, K.S.; Calaminus, G.; Lemiere, J.; Traunwieser, T.; van Santen, H.M.; Weiler, L.; Spoudeas, H.A.; Chevignard, M.
Abstract: The highest incidence rate of childhood brain tumours is in children below the age of five years, who are particularly vulnerable to the effects of treatments. The assessment of quality of survival (QoS) in multiple domains is essential to compare the outcomes for different tumour types and treatment regimens. The aim of this position statement is to present the domains of health and functioning to be assessed in children from birth to five years, to advance the collection of a common QoS data set in European brain tumour trials. The QoS group of the European Society of Paediatric Oncology (SIOP-E) Brain Tumour group conducted consensus discussions over a period of six years to establish domains of QoS that should be prioritised in clinical trials involving children under 5 years. The domains of health and functioning that were agreed to affect QoS included: medical outcomes (e.g. vision, hearing, mobility, endocrine), emotion, behaviour, adaptive behaviour, and cognitive functioning. As for children aged five years and older, a 'core plus' approach is suggested in which core assessments are recommended for all clinical trials. The core component for children from birth to three years includes indirect assessment which, in this age-group, requires proxy assessment by a parent, of cognitive, emotional and behaviour variables and both direct and indirect endocrine measures. For children from four years of age direct cognitive assessment is also recommended as 'core'. The 'plus' components enable the addition of assessments which can be selected by individual countries and/or by, age-, treatment-, tumour type- and tumour location-specific trials. Highlights: We consider the range of functioning affected by children under 5 years of age. We present domains of function with measures in use across much of Europe. We present core areas of function that should be measured in all clinical trials. We discuss additional areas of function that can be identified for specific trials.